Politics and Religion in the New Century Philosophical Reflections. - Quadrio, Philip Andrew (Sydney University Press, 2009)
Politics and Religion in the New Century contains a collection of philosophical reflections on the intersection of religion and the political in contemporary social, political and intellectual life.